Alienation and Identity Crisis in the selected Stories of Rohinton Mistry and Salman Rushdie (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Social alienation and diasporic identity were not foreign themes to the insightful writers of vibrant contemporary India. When one lives in a vast country where countless cultures are followed and diverse languages are spoken, it becomes very difficult to find and hold one’s own personal identity. It is a person’s innate disposition to migrate somewhere supposedly better and then profoundly long for where one came from. In the relentless pursuit of something superficial, we often lose something much more basic and necessary: our precious individuality. The present academic paper is a humble submission to explore the universal themes of existential identity crisis and alienation by insightfully comparing ‘The Ghost of Firozsha Baag’ by Rohinton Mistry and ‘The Free Radio’ by Salman Rushdie.The layered characters; disillusioned Ramani and marginalized Jackaline (Jaykaylee) are written by different authors, but their struggle is alike. While one alienates himself from the village by living in the delusion of having a radio, the latter has spent nearly 50 years in the same place but is still seen as an estranged outsider. They tell the poignant story of an India that was struggling, and as a result, so were its people. These stories, written by stalwarts who have faced similar tribulation in life, make these recurring themes more relatable. The concept of identity, to be specific, the search for identity becomes pivotal and one is forced to explore the sense of crisis embedded in the formation of identity. The sense of Alienation, the loss of latent self and fractured identity is some of the major areas which this paper is going to focus upon.